GASTROINTESTINAL SYMPTOMS ARE ASSOCIATED WITH SEVERITY OF CORONAVIRUS DISEASE 2019: A SYSTEMATIC REVIEW - Ardena Lianto, Lie Milka (Journal of Advanced Research in Medical and Health Science (ISSN 2208-2425), 2023)
Background:Aim: This study aims to summarize and evaluate the association between GI symptoms in COVID-19 and disease severity.Methods: A systematic search strategy was conducted across several electronic reference databases (PubMed, Cochrane Library, Google Scholar) and included articles published between 2019–2023. Duplicate publications, review articles, and incomplete articles were excluded.Results: Database searches identified a total of 17632 articles. Of these, 100 articles passed the screening process, resulting in 15 articles for full-text assessment. Among them, 6 articles did not evaluate the outcome of interest. Hence, we found 9 appropriate studies included.Conclusion: Current findings are insufficient to establish a association between GI symptoms and disease severity in COVID-19 patients.